Prevalence and Associated Risk Factors of Gestational Hypertension Among Pregnant Women in Iraq - Saeed Mohsen Al-Mosawei, Haneen; Hamid Njam, Nahawnd (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Gestational hypertension is one of the most prevalent pregnancy-related complications and poses significant risks to maternal and fatal health. The purpose of this study is to determine the prevalence of gestational hypertension in Iraqi pregnant women and to examine potential risk factors for its occurrence. Materials and Methods: This case-control research comprised 200 pregnant women in total (114 with normal blood pressure and 86 with gestational hypertension). During their prenatal clinic appointments, eligible participants were recruited using a non-random (convenience) sampling technique. Blood pressure and BMI were evaluated, and a systematic questionnaire was used to gather medical and personal information. With a significance level of p < 0.05, descriptive statistics, the Chi-square test, the t-test, and binary logistic regression were used in the analysis of the data using SPSS. Results: Gestational hypertension was identified in 43% of the study population, which is a relatively high rate that highlights the critical importance of treating this illness in basic healthcare programs. Significant correlations between prenatal hypertension and a number of characteristics, such as maternal age, gestational age, BMI, parity, and a family history of hypertension, were found by statistical analysis. However, there was no significant correlation found between the condition and characteristics like educational attainment, history of miscarriage, gestational diabetes, area of living (rural versus urban), or usage of hormonal contraceptives. Conclusion: The results imply that obesity are important modifiable factors that contribute to the development of gestational hypertension. Thus, the study highlights the importance of prompt treatment interventions, frequent medical follow-up, and health education as effective preventive measures, especially for high-risk women. The study suggests that in order to improve generalizability and gain a deeper understanding of the factors impacting this condition in pregnant women, larger, more representative samples from different parts of Iraq should be used in future research.